2021
DOI: 10.1108/itse-02-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of personality traits on perceived usability evaluation of e-learning platforms

Abstract: Purpose The purpose of this paper is to investigate the impact of personality traits on the perceived usability evaluation of e-learning platforms. In specific, perceived usability levels of the educational platforms and tools used in primary and secondary education in Greece are demonstrated. The impact which personality traits and other individual-related factors have on the perceived usability were also examined. Design/methodology/approach In total, 2,239 Greek primary and secondary education teachers pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…It gives a result between 0-100. SUS has a wide popularity because of having perfect psychometric properties [106] and providing evaluation to any technological tool such as mobile applications, web portals, online training systems high validity and reliability [107].…”
Section: Discussion On Evaluation Tools and Their Results Of The Studiesmentioning
confidence: 99%
“…It gives a result between 0-100. SUS has a wide popularity because of having perfect psychometric properties [106] and providing evaluation to any technological tool such as mobile applications, web portals, online training systems high validity and reliability [107].…”
Section: Discussion On Evaluation Tools and Their Results Of The Studiesmentioning
confidence: 99%
“…Kortum and Oswald (2018) evaluating 20 products with SUS in a sample of 268 participants found that openness to IJILT 39,1 experience and agreeableness had the strongest positive correlations with usability evaluation. Vlachogianni and Tselios (2021a), investigating the impact of personality traits on the perceived usability evaluation of various e-learning platforms, found for Zoom platform that agreeableness was the only factor that correlated with SUS score (r s 5 0.504, p 5 0.047, s). Oliveira et al (2013), evaluating mobile phone services in a data set of 603 users, found that extraversion (β 5 0.28, p 5 0.004) and conscientiousness (β 5 0.25, p 5 0.005) had a significant positive effect on users' perceived usability.…”
Section: Personality and Perceived Usabilitymentioning
confidence: 99%
“…Being able to navigate around diverse technologies is heralded as a 21st‐century skill and an essential asset for students (Guven Ozdemir & Sonmez, 2021; Heinonen et al, 2019; Vlachogianni & Tselios, 2022). In this digital world, modern technologies enhance the quality of teaching and learning through the provision of rich pedagogical approaches (Heinonen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%